Preoperative Physical Therapy Education Reduces Time to Meet Functional Milestones After Total Joint Arthroplasty. Issue 1 (January 2018) - Soeters, Rupali; White, Peter B.; Murray-Weir, Mary; Koltsov, Jayme C. B.; Alexiades, Michael M.; Ranawat, Amar S.
Abstract: Background: As length of stay decreases for total joint arthroplasty, much of the patient preparation and teaching previously done in the hospital must be performed before surgery. However, the most effective form of preparation is unknown. This randomized trial evaluated the effect of a one-time, one-on-one preoperative physical therapy education session coupled with a web-based microsite (preopPTEd) on patients' readiness to discharge from physical therapy (PT), length of hospital stay, and patient-reported functional outcomes after total joint arthroplasty. Questions/purposes: Was this one-on-one preoperative PT education session coupled with a web- based microsite associated with (1) earlier achievement of readiness to discharge from PT; (2) a reduced hospital length of stay; and (3) improved WOMAC scores 4 to 6 weeks after surgery? Methods: Between February and June 2015, 126 typical arthroplasty patients underwent unilateral TKA or THA. As per our institution's current guidelines, all patients attended a preoperative group education class taught by a multidisciplinary team comprising a nurse educator, social worker, and physical therapist. Patients were then randomized into two groups. One group (control; n = 63) received no further education after the group education class, whereas the intervention group (experimental; n = 63) received preopPTEd. The preopPTEd consisted of a one-time, one-on-one session with a physical therapist to learn and practice postoperative precautions, exercises, bed mobility, and ambulation with and negotiation of stairs. After this session, all patients in the preopPTEd group were given access to a lateralized, joint-specific microsite that provided detailed information regarding exercises, transfers, ambulation, and activities of daily living through videos, pictures, and text. Outcome measures assessed included readiness to discharge from PT, which was calculated by adding the number of postoperative inpatient PT visits patients had to meet PT milestones. Hospital length of stay (LOS) was assessed for hospital discharge criteria and 6-week WOMAC scores were gathered by study personnel. At our institution, to meet PT milestones for hospital discharge criteria, patients have to be able to (1) independently transfer in and out of bed, a chair, and a toilet seat; (2) independently ambulate approximately 150 feet; (3) independently negotiate stairs; and (4) be independent with a home exercise program and activities of daily living. Complete followup was available on 100% of control group patients and 100% patients in the intervention group for all three outcome measures (control and intervention of 63, respectively). Results: The preopPTEd group had fewer postoperative inpatient PT visits (mean, 3.3; 95% confidence interval [CI], 3.0-3.6 versus 4.4; 95% CI, 4.1-4.7; p < 0.001) and achieved readiness to discharge from PT faster (mean, 1.6 days; 95% CI, 1.2-1.9 days versus 2.7 days; 95% CI, 2.4-3.0; p < 0.001) than the control group. There was no difference in hospital LOS between the preopPTEd group and the control group (2.4 days; 95% CI, 2.1-2.6; p = 0.082 versus 2.6 days; 95% CI, 2.4-2.8; p = 0.082). There were no clinically relevant differences in 6-week WOMAC scores between the two groups. Conclusions: Although this protocol resulted in improved readiness to discharge from PT, there was no effect on LOS or WOMAC scores at 6 weeks. Preoperative PT was successful in improving one of the contributors to LOS and by itself is insufficient to make a difference in LOS. This study highlights the need for improvement in other aspects of care to improve LOS. Level of Evidence: Level II, therapeutic study.